Impact of University Degree and Professor on the language learning strategies of students - M. Cristina, Santana-Quintana (Journal of Learning Styles, 2021)
This study aims to search for methodological approaches to obtain validity evidence on the autonomy of foreign language students in Higher Education. This paper questions if university students use Language Learning Strategies (LLS) and if there is a possible relationship between LLS and the variables ‘university degree’ and ‘professor’. The collection of data was conducted using the 7.0 version (ESL/EFL) of the taxonomy of Rebecca Oxford, Strategy Inventory for Language Learning survey; SPSS statistical software was used to organize and analyse data. First, the outcome showed that the students of the analysed disciplines presented an average use of LLS; then, it showed that students favour some strategies over others based on the type of university degree; and finally, it showed that there may be a relationship between the professor and the choice of LLS by the student. This study aims to obtain more empirical evidence of the conditions that allow students to take advantage of education to develop competences in learning a foreign language as well as to emphasize that professors must act by taking the appropriate measures.
Keywords: university students; language learning strategies, teaching methods, learning and teaching in higher education